Mapping the Functional Independence Measure to a multi-attribute utility instrument for economic evaluations in rehabilitation: a secondary analysis of randomized controlled trial data. Issue 21 (8th October 2020) - Peiris, Casey L.; Taylor, Nicholas F.; Watts, Jennifer J.; Shields, Nora; Brusco, Natasha K.; Mortimer, Duncan
Abstract: Purpose: To test whether the Functional Independence Measure (FIM) could be mapped to the EQ-5D-3L to give researchers a viable but "second-best" option for calculating quality-adjusted life-years (QALYs) and conducting a cost-utility analysis when only clinical outcomes have been collected. Materials and methods: Secondary analysis of repeated measures data collected during a randomized controlled trial ( n = 3506 observations) at two inpatient rehabilitation centres. Participants had a mean age of 74 (SD 13) years, 63% were women and 58% were admitted with an orthopaedic diagnosis. Ordinary least-squares regression and adjusted limited dependent variable mixture models were used to estimate regression-based mappings. Performance was evaluated based on mean absolute error and the proportion of errors in excess of the minimally important difference. Results: In orthopaedic and neurological patients, high mean absolute errors (0.2 on the quality-adjusted life years scale) and a high proportion of errors (60%) in excess of the minimally important difference suggest that predicted EQ-5D-3L values provided a poor substitute for observed EQ-5D-3L values. Conclusions: Regression-based mappings from the FIM to the EQ-5D-3L are error-prone and unsuitable for calculating QALYs in rehabilitation patients. Researchers and rehabilitation professionals should therefore include a multi-attribute utility instrument such as the EQ-5D as well as the FIM to evaluate the effect of rehabilitation interventions and in rehabilitation registries. This will provide additional information on health-related quality of life and support cost-utility analyses. Implications for rehabilitation: The Functional Independence Measure (FIM) cannot be used to calculate quality-adjusted life-years (QALYs) for cost-utility analyses. Predicting QALYs from FIM data is a poor substitute for direct measurement of QALYs in orthopaedic or neurological rehabilitation populations. Multi-attribute utility instruments (MAUIs) allow direct measurement of QALYs, as well as providing a patient-reported measure of clinical quality and outcomes in rehabilitation. A MAUI should be included routinely in clinical practice by rehabilitation professionals as well as in rehabilitation trials and registries to track patient outcomes and improve clinical practice.